2018
DOI: 10.1103/physreva.97.063823
|View full text |Cite
|
Sign up to set email alerts
|

Coherent quantum dynamics launched by incoherent relaxation in a quantum circuit simulator of a light-harvesting complex

Abstract: Engineering and harnessing coherent excitonic transport in organic nanostructures has recently been suggested as a promising way towards improving man-made light harvesting materials. However, realising and testing the dissipative system-environment models underlying these proposals is presently very challenging in supramolecular materials. A promising alternative is to use simpler and highly tunable 'quantum simulators' built from programmable qubits, as recently achieved in a superconducting circuit by Potoč… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 91 publications
3
31
0
Order By: Relevance
“…This situation, known as vibrationally assisted electronic decay or "phonon antenna" due to a sharply structured spectral density, has been studied in the context of EET in several different contexts [3,39,[66][67][68]. The bath-induced population-to-coherence process already predicted by nonsecular Redfield theory has been confirmed by HEOM simulations in the strong-coupling regime [65]. We showed that this generation of electronic coherence is the most efficient for a regime between weak and strong system-bath couplings, which is a general observation across the various types of biological "noise-assisted" transport that have been studied.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…This situation, known as vibrationally assisted electronic decay or "phonon antenna" due to a sharply structured spectral density, has been studied in the context of EET in several different contexts [3,39,[66][67][68]. The bath-induced population-to-coherence process already predicted by nonsecular Redfield theory has been confirmed by HEOM simulations in the strong-coupling regime [65]. We showed that this generation of electronic coherence is the most efficient for a regime between weak and strong system-bath couplings, which is a general observation across the various types of biological "noise-assisted" transport that have been studied.…”
Section: Introductionmentioning
confidence: 80%
“…In a recent work, we have used numerically exact hierarchical equations of motion (HEOM) [33,[56][57][58][59][60][61][62][63][64] to predict the ultrafast generation of electronic coherences during the incoherent relaxation of a high-lying excitonic state into a doublet of nearly degenerate low-lying states [65]. This process could be realized in the particular configuration of the SC qubit circuit of Potočnik et al [53] in the following way: Intersite couplings and gaps are chosen so that the firstexcited manifold consists in a bright state (optically excitable) separated from a doublet of dark (nonradiative) states such that the bright-dark energy gap is in resonance with a sharply peaked spectral density of the noise.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled to some specific qubit, the TLR can act as a reaction center through Purcell-like coupling. 40,41 By tuning the TLR's decay time and the qubit-TLR detuning, we can effectively modified the qubit's decay time through Purcell-like coupling, according to Equation (18).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…On the other hand, much progress has been made in quantum information science, inspiring several interesting quantum simulation 35,36 experiments to verify the design principles for optimal light-harvesting. 28,29,[37][38][39][40][41][42] By using bath engineering and the gradient ascent pulse engineering algorithm, Wang et al 37 performed an experimental quantum simulation of photosynthetic energy transfer by using nuclear magnetic resonance (NMR). It was demonstrated that the open quantum dynamics in an N-level system, with arbitrary Hamiltonian and bath spectral density, can be effectively emulated by an NMR system with log 2 N qubits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation